HASIL TANGKAPAN PER UPAYA DAN POTENSI MAKSIMUM LESTARI IKAN MADIDIHANG (Thunnus albacares) YANG DIDARATKAN DI PELABUHAN PERIKANAN SAMUDERA (PPS) KENDARI - Ahmad Nuramin; Andi Irwan Nur; Latifa Irwan Fekri (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
If the use of yellowfin fish is not controlled now, it will threaten the sustainability of the resource in the future.The purpose of the study was to analyze the catch per effort and maximum sustainable potential of madidihang fish landed at Kendari Ocean Fishing Port. The method in the study was a survey with descriptive analysis. The results showed that the CPUE value of madidihang fish equivalent to pole and line fluctuated from 2016-2022. In 2017 there was an increase with a value of 1,831 kg/trip and in 2019 there was a decrease with a value of 624 kg/trip. The maximum sustainable potential results of using the Schaefer and Fox model of the optimum catch effort (FMSY) value of 1,913 trips, 1,562 trips and maximum catch value (CMSY) of 2,459,467 kg / year or 2,459 tons / year, 2,341,013 kg / year or 2,341 tons / year. The stock status of madidihang fish in the Banda Sea experienced overfishing in 2016, 2017 and 2018.